1973
DOI: 10.1099/00221287-79-2-311
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intracellular and Extracellular Neutral and Alkaline Proteases in Aspergillus nidulans

Abstract: S U M M A R YSynthesis and secretion of extracellular neutral and alkaline proteases in Aspergillus nidulans are repressed in the presence of low molecular weight sources of carbon, nitrogen and sulphur; protease is formed and released when the medium is deficient for any one of these elements. Induction of protease by exogenous protein does not occur.Activation of intracellular protease is repressed by sources of carbon, nitrogen, sulphur and phosphorus, activation taking place when any one is deficient.These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 12 publications
1
61
0
2
Order By: Relevance
“…In view of the fact tbat production of proteolytic enzymes is subject to catabolite repression it might be predicted that the presence of free carbon would inhibit proteolytic activity. However, in studies of protein production by Aspergillus Cohen (1973) showed that the enzymes were secreted when the growth medium was deficient in any one of the low molecular weight sources of C, N and S. In the present case induction of enzyme production may be attributable to the absence of N compounds of low molecular weight. 'Starter' carbon may be required as an energy source for enzyme synthesis or as a component of the molecular structure of the enzyme.…”
Section: Discussionmentioning
confidence: 85%
“…In view of the fact tbat production of proteolytic enzymes is subject to catabolite repression it might be predicted that the presence of free carbon would inhibit proteolytic activity. However, in studies of protein production by Aspergillus Cohen (1973) showed that the enzymes were secreted when the growth medium was deficient in any one of the low molecular weight sources of C, N and S. In the present case induction of enzyme production may be attributable to the absence of N compounds of low molecular weight. 'Starter' carbon may be required as an energy source for enzyme synthesis or as a component of the molecular structure of the enzyme.…”
Section: Discussionmentioning
confidence: 85%
“…The production of proteases appeared to be subjected to control easily ei-100 SAMARNTARN, CHEEVADHANARAK, and TANTICHAROEN Vol. 45 ther by metabolites repression/derepression or proteinaceous induction, or by the combination of both in several fungi (Cohen, 1973;Cohen et al, 1975;Farley and Ikasari, 1992;Lasure, 1980;North, 1982). Thus it is likely that the high production of alkaline protease in BDS medium involved the slow hydrolyzation and/or the proteinaceous component(s) of defatted soybean.…”
Section: Defatted Soybean As Substrate For Alkaline Protease Productionmentioning
confidence: 99%
“…Putative disruptants were identified using a PCR screening technique; spores were inoculated in 2 ml complete medium and the cultures were incubated overnight at 30°C. The mycelial mat was harvested, freeze dried, and dissolved in an extraction buffer described by de Graaff et al (1988). After phase separation, 10 pl of the liquid phase was used for PCR reactions using a Sensa 949E PCR apparatus and PCR conditions were those recommended for Taq polymerase (Pharmacia).…”
Section: Molecular Methodsmentioning
confidence: 99%
“…A. niger chromosomal DNA was isolated according to de Graaff et al (1988), digested with restriction enzymes, separated by agarose gel electrophoresis on 0.8 % (mass/vol.) agarose, and blotted onto a nylon membrane (Hybond N') via capillary elution according to Sambrook et al (1989).…”
Section: Molecular Methodsmentioning
confidence: 99%
See 1 more Smart Citation